2021
DOI: 10.3390/medicina57121379
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Modulated Arc Therapy Capabilities for Treating Lower-Extremity Skin Affected by Several Merkel Cell Carcinoma Nodules: When Technological Advances Effectively Achieve the Palliative Therapeutic Goal while Minimising the Risk of Potential Toxicities

Abstract: The peculiar and rare clinical condition below clearly requires a customized care approach in the context of personalized medicine. An 80-year-old female patient who was subjected in 2018 to surgical removal of a cutaneous Merkel cell carcinoma (MCC) nodule located on the posterior surface of the left thigh and to three subsequent palliative radiotherapy treatments developed a fourth relapse in October 2020, with fifteen nodular metastases located in the left thigh and leg. Since the overall macroscopic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The study showed that lymph node irradiation alone to the microscopic and macroscopic positive regional lymph nodes conferred an excellent regional control rate that was comparable to that of lymphadenectomy. Another study proved that lower dose ranges (30/40 Gy in 2 Gy/day/fractions) were sufficient to stably control extensive skin involvement of large body areas when symptom palliation was the primary goal of radiotherapy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that lymph node irradiation alone to the microscopic and macroscopic positive regional lymph nodes conferred an excellent regional control rate that was comparable to that of lymphadenectomy. Another study proved that lower dose ranges (30/40 Gy in 2 Gy/day/fractions) were sufficient to stably control extensive skin involvement of large body areas when symptom palliation was the primary goal of radiotherapy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomas have traditionally been considered to be radioresitant; however, RT has now been routinely incorporated into sarcoma treatment regimens for more than a century ( 27 ). The introduction of newer RT modalities, such as IGRT, intensity modulation RT, volumetric modulated arc therapy, stereotactic RT, and proton-based RT has revolutionized the field of radiation oncology, while resulting in fewer toxicities ( 8 , 27 , 28 ). Given the locally aggressive nature of the tumor and risk of local and distant recurrence, several authors recommend surgery with concomitant radiotherapy as the standard of care for MPNSTs ( 3 , 4 , 14 , 29 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our GTVs ranged from 10 to 209 cc, while CTVs from 25 to 3744 cc. The largest CTV refers to the whole skin of the left lower limb of a patient in whom previous three RT courses had failed to prolong PFS, as described in [ 22 ]. Palliative doses were the most common, having been used in 6/8 patients: by delivering a 3 Gy/day fraction, a total dose of 30 Gy was administered to 5 patients and 36 Gy to another one.…”
Section: Discussionmentioning
confidence: 99%